Erratum. Issue 1 (February 2015) - Unknown
Stent fracture and occlusion after treatment of symptomatic vertebral artery ostium stenosis with a self-expanding device: A case report by Jun Lu, Jiachun Liu, Daming Wang and Shuo Wang, Interventional Neuroradiology 2014 20: 755–760, DOI:10.1177/INR-2014-10068 . In the above article the author affiliations were listed incorrectly, the correct version is listed below: Jun Lu 1, Jiachun Liu 2, Daming Wang 2 and Shuo Wang 1 1 Department of Neurosurgery, Beijing Tiantan Hospital, Capital Medical University, Beijing, China 2 Department of Neurosurgery, Beijing Hospital, Beijing, China